2013
DOI: 10.1080/01690965.2011.572401
|View full text |Cite
|
Sign up to set email alerts
|

The source ambiguity problem: Distinguishing the effects of grammar and processing on acceptability judgments

Abstract: Judgments of linguistic unacceptability may theoretically arise from either grammatical deviance or significant processing difficulty. Acceptability data are thus naturally ambiguous in theories that explicitly distinguish formal and functional constraints. Here, we consider this source ambiguity problem in the context of Superiority effects: the dispreference for ordering a wh-phrase in front of a syntactically “superior” wh-phrase in multiple wh-questions, e.g. What did who buy? More specifically, we conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 94 publications
10
79
0
Order By: Relevance
“…it is highly plausible that the retrieval of the extracted wh-element (which problem) is eased by the fact that problems can be solved, therefore providing a good semantic match to the object retrieval process triggered by the verb, whereas students cannot be solved, therefore providing a poor match, and reducing interference. This hypothesis is supported by a series of studies conducted by Hofmeister and colleagues (e.g., Hofmeister et al, 2007Hofmeister et al, , 2013, in which they found that increasing the syntactic and semantic complexity of the extracted element eases its retrieval and increases the acceptability of the sentence. For instance, using cleft constructions (e.g., It was a(n) (alleged Venezuelan) communist who the members of the club banned from ever entering the premises), they observed faster reading times after the embedded verb banned in sentences requiring the retrieval of complex objects (an alleged Venezuelan communist) as compared to those requiring the retrieval of simple objects (a communist) (Hofmeister et al, 2007).…”
Section: Featural Rm and Weak Islandssupporting
confidence: 60%
See 2 more Smart Citations
“…it is highly plausible that the retrieval of the extracted wh-element (which problem) is eased by the fact that problems can be solved, therefore providing a good semantic match to the object retrieval process triggered by the verb, whereas students cannot be solved, therefore providing a poor match, and reducing interference. This hypothesis is supported by a series of studies conducted by Hofmeister and colleagues (e.g., Hofmeister et al, 2007Hofmeister et al, , 2013, in which they found that increasing the syntactic and semantic complexity of the extracted element eases its retrieval and increases the acceptability of the sentence. For instance, using cleft constructions (e.g., It was a(n) (alleged Venezuelan) communist who the members of the club banned from ever entering the premises), they observed faster reading times after the embedded verb banned in sentences requiring the retrieval of complex objects (an alleged Venezuelan communist) as compared to those requiring the retrieval of simple objects (a communist) (Hofmeister et al, 2007).…”
Section: Featural Rm and Weak Islandssupporting
confidence: 60%
“…If so, we would expect lexical restriction to affect superiority violations configurations in the same way it affects configurations of intervention. However, this does not seem to be the case, as some recent findings by Hofmeister et al (2013) attested. In four experiments (two acceptability judgment and two self-paced reading experiments), the authors explored the role of lexical restriction in structures involving Superiority violations (Pesetsky, 2000).…”
Section: Relativized Minimality and Superioritymentioning
confidence: 61%
See 1 more Smart Citation
“…However, a less than perfect match can make VPE harder to interpret (i.e. recover a meaning for), and therefore degraded in terms of acceptability (for other proposals linking processing complexity with degraded acceptability, see Arregui et al 2006;Hofmeister et al 2013). We refer to this as a structural constraint, since it essentially builds into the semantic representation information about voice alternations, which we take to be a canonical syntactic alternation.…”
Section: What a Theory Of Vpe Should And Shouldn't Account Formentioning
confidence: 99%
“…For example, in the study of sentences with "island violations" -sentences where a linguistic dependency in a particular syntactic configuration is judged to be unacceptable -both processing factors and grammatical constraints have been proposed to account for the unacceptability (Ross 1967;Chomsky 1973Chomsky , 1977Chomsky , 1981Chomsky , 1986Kluender 1992Kluender , 1998Kluender & Kutas 1993;Phillips 2006;Hofmeister & Sag 2010;Sprouse, Wagers, & Phillips 2012;Hofmeister, Jaeger, Arnon, Sag, & Snider 2013;Hofmeister, Staum Casasanto, & Sag in press;Sprouse & Hornstein In press). Generally speaking, knowing when processing differences are at play in acceptability contrasts is an essential ingredient to a more comprehensive understanding of the relationship between formal and functional factors.…”
mentioning
confidence: 99%